The Crow (1994): James O'Barr revisto por Alex Proyas - Fiori, Fernando Martins (2017)
This work investigates the process of creation and transposition between two artistic works, presenting the dialogue between the language of comics and cinema. The main corpus consists of the grahic novel, The Crow (1988), conceived by James O'Barr, and its transposition for the cinema, in 1994, under the direction of Alex Proyas. It will be approached ancient myths and other representations, such as the poem, The Raven, by Edgar Allan Poe, that involve the symbolism of crow in different languages. Somehow, they interfere and are relevant for the chosen corpus. The methodology consists, mainly, of the books Gesto Inacabado (1998) by Cecilia Almeida Salles and Intersemiotic Translation (2013) by Júlio Plaza.